Highly active and reusable catalyst from Fe-Mg-hydrotalcite anionic clay for friedel-crafts type benzylation reactions - Choudhary, Vasant R.; Jha, Rani; Choudhari, P. A. (Journal of Chemical Sciences, 2005)
Fe-Mg-hydrotalcite (Mg/Fe = 3) anionic clay with or without calcination (at 200-800 degrees C) has been used for the benzylation of toluene and other aromatic compounds by benzyl chloride. Hydrotalcite before and after its calcination was characterized for surface area, crystalline phases and basicity. Both the hydrotalcite, particularly after its use in the benzylation reaction, and the catalyst derived from it by its calcination at 200-800 degrees C show high catalytic activity for the benzylation of toluene and other aromatic compounds. The catalytically active species present in the catalyst in its most active form are the chlorides and oxides of iron on the catalyst surface.
Keywords: activation by calcinations; benzylation of aromatic compounds; benzylation of toluene; Fe-Mg-hydrotalcite